(untitled) (Indian Journal of Nematology, 2024)
Plant parasitic nematodes (PPNs) pose significant threats to global agriculture, causing annual losses exceeding USD 150 billion. Chemical nematicides, once the primary method for PPN control, are now restricted due to environmental and health concerns. Consequently, there is a pressing need for eco-friendly alternatives. Biological agents, particularly botanical nematicides and microbial volatile organic compounds (VOCs), have emerged as promising solutions. VOCs, produced by bacteria and fungi, have garnered attention for their effectiveness against PPNs. These compounds, with diverse chemical compositions, exhibit various modes of action, including fumigant toxicity, repellent activity, and inhibition of egg hatching. Notably, Bacillus and Pseudomonas species have shown significant nematicidal activity through VOC emission. Additionally, fungal VOCs, particularly those from Fusarium and Trichoderma spp., have demonstrated efficacy against PPNs. Molecular docking studies have highlighted specific compounds, such as benzoic acid and dimethyl disulfide, as effective against nematode protein targets. Integrating in vitro assays with computational analyses offers insights into the mechanisms underlying VOC-mediated nematode control. However, further research is needed to validate VOC efficacy under field conditions and elucidate their molecular impact on nematodes. This review provides a comprehensive overview of the current research on bacterial and fungal VOCs and their potential applications in PPN management, highlighting the need for continued investigation to develop sustainable solutions for nematode control.